APLIKASI PENGHITUNG KALORI TERBAKAR SAAT BEROLAHRAGA SEPEDA MENGGUNAKAN GLOBAL POSITIONING SYSTEM (GPS) BERBASIS ANDROID - Dwi Fitriyanti, Aris (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2013)
Android technology development is very fast these days , people used to support activities in various fields , one of them in the field of sports . To maintain the condition of your body to stay healthy in the midst of a solid activity , some people take the time and costs more to exercise in the fitness center . But they often feel bored because there is always exercising indoors , it makes some people choose sports that can provide fun , lively sports are cycling a few years.In the fitness center , the user can exercise bike burn calories by looking at the calories spent on the tool , because by looking at the results of the sports activities we can evaluate how adaptable our sport . With the issues that needed applications that can help people to still be able to evaluate and monitor their cycling activities such as speed , mileage , travel time , and calories burned on the go . Android is a rapidly evolving technology that today, almost all mobile products now have the android operating system , and many are using this technology . Burned calorie counter application is based on android that can be used anytime and anywhere they are cycling, so as to save costs.The results of this study are expected to be more motivated people to live more healthy by exercising , people can evaluate their cycling activities whenever they are cycling , also exercising with a happy heart because it is supported by android technology that they have.Â Keywords : calories burned, android, application, sport bike